Otorhinolaryngology Foundation: Three Decades of Excellence in Education, Research, and Scientific Advancement - Ricardo Ferreira Bento; Adilson Marcos Montefusco; Greice Vitória Garcia Ribeiro; Annita Luz Lacerda Lowndes; Adriana de Almeida Fozzati (International Archives of Otorhinolaryngology)
Introduction The Otorhinolaryngology Foundation (FO), created in 1995, has played an important role in the advancement of otorhinolaryngology in Brazil, through initiatives in education, research, and service provision.